Efektivitas Kerentanan Penyelewangan Distribusi Dana Bantuan Sosial dan Dampaknya Terhadap Kesejahteraan Masyarakat di Kabupaten Ciamis - Iwan Ridwan Paturchman; Aqila Nazeeya Putri; Nazmi Fatimah Azahra; Yolanda Salsa Aulia (Kampus Akademik Publiser, 2026)
This study examines the effectiveness of social assistance distribution and the vulnerability to misuse in rural areas, focusing on a case study in Ciamis Regency. Social assistance programs are designed to reduce poverty and maintain purchasing power among low-income households. However, implementation challenges such as data inaccuracies, weak inter-agency coordination, and limited community oversight often create opportunities for misuse. This research applies a qualitative case study approach using interviews and field observations to explore the distribution mechanism, identify potential risks of corruption, and analyze socio-economic impacts on beneficiaries. The findings reveal that although administrative procedures have been formally implemented, significant issues remain in data validation, leading to inclusion and exclusion errors. Furthermore, high discretionary power at the village level combined with limited transparency increases the likelihood of opportunistic behavior. The study also finds that misuse of social assistance negatively affects economic stability, social cohesion, and public trust in local institutions. Theoretically, the findings support the relevance of the principal-agent problem and fraud triangle theory in explaining corruption risks in public sector programs. Practically, this study recommends strengthening data integration, improving participatory monitoring systems, and enhancing institutional accountability to ensure more effective and equitable distribution of social assistance.